Termination of a permit to operate a pharmaceutical wholesaler - Kiedrzynek, Michał (Studia Iuridica Toruniensia, 2025)
Health protection is one of the most important tasks of public authorities. In order to comprehensively and effectively perform the tasks entrusted to them, many legal acts have been created regulating detailed issues concerning health protection, including ensuring the safety of manufacturing and trade in medicinal products. An inseparable element of drug distribution are pharmaceutical wholesalers, which act as intermediaries between drug manufacturers and pharmacies. Their functioning is subject to many requirements, among which the need to obtain a permit is one of the most important. However, the permit does not create irreversible effects, which is why it is possible for it to cease. When creating the conditions for the termination of the permit to run a pharmaceutical wholesaler, the legislator provided for several circumstances, the occurrence of which results in the mandatory withdrawal of the permit or authorizes the competent authority to withdraw it optionally. The legislator often uses imprecise wording, which is why there are many doubts about interpretation. Analyzing both current and past regulations, one can also draw several conclusions regarding the changes taking place and their probable future direction.